Calculadora da pegada hídrica residencial. - ROCHA, Clarissa Maria Ramalho de Sá. (2014)
Submitted by Maria Medeiros (maria.dilva1@ufcg.edu.br) on 2018-06-11T12:17:49Z No. of bitstreams: 1 CLARISSA MARIA RAMALHO DE SÁ ROCHA - DISSERTAÇÃO (PPGRN) 2014.pdf: 2577840 bytes, checksum: 7a2f611d9e68c547c369f0cb15925498 (MD5)